High moisture tempering of corn before flaking: effects on bacterial contamination from houseflies and fecal shedding in finishing cattle - Broce, A.B.; Gordon, C.M.; Sindt, J.J.; Depenbusch, Brandon E.; Drouillard, James S.; Phebus, Randall K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Tempered and non-tempered steam-flaked corn samples along with total mixed rations containing either tempered or non-tempered steam-flaked corn were exposed to flies and the environment for 21 hours. Exposure to flies and the environment increased (P<0.05) generic E. coli, non-E. coli coliforms, total coliforms, and total plate count for the steamflaked corn samples independent of tempering. Tempering corn before steam-flaking increased total plate counts. Exposure to the environment and flies did not significantly (P>0.05) alter microbial counts of total mixed rations regardless of tempering (Table 1). Generic E. coli coliforms were greater in total mixed rations when the corn was tempered, both before and after exposure to flies and the environment (P<0.05). Similarly, total microbial plate counts were higher in steam-flaked corn samples when the corn was tempered (P<0.05). A significant increase in response to grain tempering was also noted in non-E. coli coliforms and total microbial plate counts for the total mixed ration samples after exposure (Table 1). Following the initial experiments, 96 finishing beef steers were used to evaluate the effects of tempering steam-flaked corn on acid-resistant E. coli and total fecal coliforms. On day 56 of the feeding period, fecal samples were collected and analyzed for total and acidresistant E. coli and coliforms. No significant treatment difference was observed in the total fecal coliforms (P>0.05), but acid-resistant (pH 2) non-E. coli and total fecal coliforms (Table 2) were lower in feces of cattle fed the tempered grain than those fed non-tempered grain.
Keywords: Beef; Corn; Flaking; Houseflies; Fecal matter; Finishing cattle; Coliforms